Alternatiewe tot apartheid? Gespreksgroepe in die Nederduitse Gereformeerde Kerk (NGK) gedurende die 1980s - Van der Merwe, Barend; Oelofse, Marietjie (Faculty of Humanities, University of the Free State, 2013)
During the 1980s, the South African government was struggling to keep violence in the country under control despite the many reforms that the PW Botha regime has brought with it. The days of “’grand apartheid”, associated in particular with HF Verwoerd and the controversial homeland system, was over but certain key apartheid laws were still upheld. The government tried to create the impression that the policy of apartheid was a thing of the past, while on the other hand it was retaining political power. While the government made important changes to the apartheid policy, the Dutch Reformed Church also felt pressure from all sides due to its particular role in the development and sustainment of the apartheid regime. Lacking official channels, frustrated theologians and members of the Church resorted to informal discussion groups to initiate a think tank about the future of the Church and the country as a whole.
Keywords: Dutch Reformed Church; Apartheid; National Party; General Synod; Dutch Reformed family of churches; Informal discussion groups; Nederduitse Gereformeerde Kerk